Doing GenderBody and Gendered Probation. A Case (Re)Constructive Analysis of Gendered Probation - Kirchner, Anna; Zizek, Boris (ETHICS IN PROGRESS, 2023)
With the present article an extension of the doing gender concept by another important dimension, the body, is proposed. Butler showed that sex results from the materialization and we argue that not only gender emerges from interactive doing, but also does sex. This process is called Doing GenderBody and interestingly we showed that it is not done by doing the gender. After the inactive production of a gender/sex, it follows an evaluation process of this produced gender/sex, called the probation. Moreover, this gender/sex must be a valuable contribution to the community. The valency of the probation figure does not only depend on the collective view, but also on a produced sex/gender which contradict the shared gender/sex knowledge. Further, because of this contradiction the single person sees this as a valuable contribution to the community. The analysis of the art works we have done allowed us to show the fundamental modes of the possibility for probation figures to be constructed.